Performance of different potato varieties under plastic mulching conditions at Dailekh, Nepal - Paudel, Asmita; Pandey, Krishna Raj; Joshi, Yagya Raj; Mahato, Anju (Fundamental and Applied Agriculture, 2023)
Mulching helps to preserve soil fertility by preventing moisture loss, main- taining soil temperature, limiting weed growth, promoting microbial growth, and minimizing soil erosion. An experimental study was conducted to assess the effect of plastic mulching and control conditions (as main factors) on yield attributes of five potato varieties, namely Khumal Seto-1, Desiree, Cardinal, Kufri-Jyoti, and C-88 (as sub-factors), in Dailekh, Nepal. A Split-plot design was employed comprising altogether ten treatments with three replications each. R-Studio software was used to analyze the data and attribute the responses to growth and yield parameters. The Duncan’s Multiple Range Test (DMRT) was used to differentiate the treatment means at 5% level of significance. Mulching treatment was found to be significantly more effective than no mulch for all the vegetative growth attributes. Compared to no mulch, the use of plastic mulch produced the greatest plant height (38.66 cm) at 75 DAS, highest number of marketable tubers (11.64), and the total number of tubers per hill (13.04), marketable tuber yield (3.93 kg/m2), and a significantly higher total tuber yield of 25.48 t/ha. Similarly, total tuber yield was found to be highest for Khumal Seto-1 (25.32 t/ha) and least for Kufri-Jyoti (22.38 t/ha). The benefit-cost analysis was found to be significant for the mulch condition and Khumal Seto-1, with promising ratios of 3.28 and 3.48, respectively. Thus, Khumal Seto-1 under plastic mulching may be used for better productivity of potatoes in Dailekh, and moreover, other readily available and accessible mulch options, including organic mulch-materials, can be utilized.